2002
DOI: 10.1046/j.1365-2133.2002.04541.x
|View full text |Cite
|
Sign up to set email alerts
|

Arrector pili muscle: evidence of proximal attachment variant in terminal follicles of the scalp

Abstract: Terminal follicles of the human scalp may also present this variant of proximal insertion of the AP muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…7,8 Recent evidence shows that fascicles of the AP muscle may surround the entire circumference of some hair follicles at the bulge area. 9,10 Studying the anatomy of FUs in horizontal sections, we recently reported 4 that the AP muscle displays a clear relationship to the follicular unit, forming a common thick bundle which is always oriented towards the same pole in different FUs. Based on these findings, we hypothesised that the AP muscles form a single structure that is shared by the follicles contained in each follicular unit.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent evidence shows that fascicles of the AP muscle may surround the entire circumference of some hair follicles at the bulge area. 9,10 Studying the anatomy of FUs in horizontal sections, we recently reported 4 that the AP muscle displays a clear relationship to the follicular unit, forming a common thick bundle which is always oriented towards the same pole in different FUs. Based on these findings, we hypothesised that the AP muscles form a single structure that is shared by the follicles contained in each follicular unit.…”
Section: Discussionmentioning
confidence: 99%
“…While the APM is known to attach to the bulge via a tendon, the tendon cells have not been identified (Barcaui et al, 2002; Guerra Rodrigo et al, 1975). We showed that the tendon/ligament extracellular matrix protein periostin (Horiuchi et al, 1999; Norris et al, 2007) was strongly expressed in bulge stem cells and deposited locally around the bulge.…”
Section: Discussionmentioning
confidence: 99%
“…Narisawa & Kohda (1993) reported that thin fibres of the AP muscle closely encircled the entire circumference of the facial vellus hair at the bulge area. Another study found that the bundles of the AP muscle encircled the entire terminal hair follicle at the bulge level, which was described as a variation (Barcaui et al. 2002).…”
Section: Discussionmentioning
confidence: 99%